The types and functions of code-switching among Malay bilinguals / Alinda Abdul Rashid - Alinda , Abdul Rashid (2019)
Code-switching is a communicative strategy used by bilingual and multilingual speakers where two or more languages are used. Malaysia is a perfect example of a country where code-switching is a common phenomenon among its people, due to its multilingual and diversified cultural communities. The aim of this study is to identify and determine the types and functions of Malay-English and English-Malay code-switching instances observed from interactions among 12 Malaysian bilingual students of a private college in Kuala Lumpur. The theoretical frameworks adopted in the study are Poplack‟s (1980) three types of code-switching and Appel and Muysken‟s (2006) six functions of code-switching. The data were collected through questionnaires, recorded observations and interviews. The findings revealed that participants used more intra-sentential switches compared to inter-sentential and tag switches. The findings also show that among the reasons that prompt Malaysian bilingual students to code-switch include compensating for lack of equal translation, quoting somebody else, making an interjection, repeating to clarify, expressing group solidarity and providing emphasis. In addition, it was found that most of the participants code-switch frequently and subconsciously. By understanding the different types and functions of code-switching, it is hoped that the findings from this study will provide more insights into the phenomenon of code-switching among Malaysian bilinguals.